2018
DOI: 10.4102/jsava.v89i0.1666
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies against Schmallenberg virus detected in cattle in the Otjozondjupa region, Namibia

Abstract: Several ruminant species have been shown to be susceptible to Schmallenberg virus (SBV), but adult animals usually recover after showing mild or no clinical signs. However, transplacental infection can occur and lead to abortion, malformations and stillborn lambs, calves and goat kids. During November and December 2014, malformations were observed in 11 stillborn calves from two farms in the north-eastern region of Namibia. Blood samples were collected from 9 of the 11 cows that delivered stillborn and malform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The Schmallenberg virus RNA was also recently detected in Culicoides pools as well as in malformed livestock in Israel [ 31 ]. Antibodies to SBV have been reported in ruminants of neighboring countries of Namibia [ 32 ] and Mozambique [ 33 ], indicating the virus may be circulating in southern Africa; however, the close relationship with other members of this group, such as is apparent from our study, may also suggest possible cross reactivity of antibodies in the Simbu serogroup [ 34 ]. The Ingwavuma virus was the only virus not from clade B in the Simbu serogroup.…”
Section: Discussionmentioning
confidence: 52%
“…The Schmallenberg virus RNA was also recently detected in Culicoides pools as well as in malformed livestock in Israel [ 31 ]. Antibodies to SBV have been reported in ruminants of neighboring countries of Namibia [ 32 ] and Mozambique [ 33 ], indicating the virus may be circulating in southern Africa; however, the close relationship with other members of this group, such as is apparent from our study, may also suggest possible cross reactivity of antibodies in the Simbu serogroup [ 34 ]. The Ingwavuma virus was the only virus not from clade B in the Simbu serogroup.…”
Section: Discussionmentioning
confidence: 52%
“…In 2016, SBV re-emerged and recirculated in Ireland, the UK and in Belgium [27–29] resulting in a second outbreak of abortions and congenital malformations in ruminants. SBV was also confirmed in regions that had previously been unaffected by SBV (north and north west of Ireland [30]), and in countries outside of the EU [3138], highlighting the continued geographical expansion of SBV. The virus continued to circulate in Ireland and the UK in 2017, which is in contrast with other European countries which have not (yet, September 2019) reported notable SBV circulation during this time (Fig.…”
Section: Introductionmentioning
confidence: 92%
“…A model for the transmission of SBV between regions in Europe suggested that vector dispersal is the principal mechanism for transmission of SBV, even at the continental scale [219]. More recently, SBV has been reported in countries outside of Europe, including Azerbaijan [31], China [32], Ethiopia [33, 34], Iran [35], Lebanon [36], Namibia [38] and Mozambique [31, 37] suggesting possible geographical expansion of SBV. However, reports of SBV emergence in new geographical regions which are based solely on serological detection of SBV antibodies, particularly when samples originate in regions where other Simbu viruses are known to be enzootic, should be interpreted cautiously as some ELISAs can have cross-reactivity between SBV and other Simbu viruses [114].…”
Section: Introductionmentioning
confidence: 99%
“…The original source of SBV is still unclear; however, there are reports of SBV cross-reactive antibodies to other Simbu serogroup viruses found in African cattle, prior to and after the initial European outbreak [18,19,20]. A report from Jordan in 2013 indicated detection of antibodies against Aino virus, another Simbu serogroup virus, in ruminants on farms where similar clinical symptoms associated with SBV infections were observed [21].…”
Section: Epidemiologymentioning
confidence: 99%